2018
DOI: 10.1177/2374373518770805
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers Affecting Adherence Among People Living With HIV/AIDS: A Qualitative Perspective

Abstract: Background: It is widely accepted that for HIV-positive persons on highly active antiretroviral treatment, high levels of adherence to treatment regimens are essential for promoting viral suppression and preventing drug resistance. Objectives: This qualitative study examines factors affecting the adherence to HIV/AIDS treatment among patients with HIV/AIDS at a local hospital in Malaysia. Methods: The data from purposefully selected patients were collected by in-depth interviews using a pretested interview gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
3
18
1
Order By: Relevance
“…The personal level factors that enhance ART adherence include positive results from the treatment [9], faith in treatment [10], and improved understanding of the disease process [11]. Likewise, improvement in CD4 count and clinical conditions is highly associated with good adherence [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The personal level factors that enhance ART adherence include positive results from the treatment [9], faith in treatment [10], and improved understanding of the disease process [11]. Likewise, improvement in CD4 count and clinical conditions is highly associated with good adherence [9].…”
Section: Introductionmentioning
confidence: 99%
“…ALHIV who witness clinical improvement after starting ART are motivated to be adherent to medication [12]. The motivation to adhere to medication is also high when peers living with HIV who are on ART exhibit an improved health status [11]. The provision of appropriate education and motivation from the doctors, reduction in pill burden, peer and community support further contribute to improved adherence patterns [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies published show that family-caregiving often leads to emotional, physical, social and financial burdens, resulting in families experiencing significant stress. Other studies showed that family-caregiving remains a predominantly feminine activity, attributed to several societal and cultural demands on women (Ahmed et al, 2018;Sharma et al, 2016). Other published studies found that the support that caregivers provided positively impacted on the recipients' quality of life, and resulted in a significant cost-saving with regard to the healthcare system (Lambert et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Self‐efficacy for managing disease (how well an individual perceives their personal capability for taking specific actions to manage disease; Bandura, Barbaranelli, Caprara, & Pastorelli, 1996; Lorig, Sobel, Ritter, Laurent, & Hobbs, 2001) has been shown to have a close relationship with adaptation outcomes. Self‐efficacy for managing HIV is of great importance for adaptation outcomes for PLWH, as it is vital to decisions about the range of their self‐management activities, which are in turn strongly linked to enhanced quality of life, less adverse symptoms and better ART adherence (Ahmed, Farooqui, Syed Sulaiman, Hassali, & Lee, 2019; Angwenyi, Aantjes, Bunders‐Aelen, Lazarus, & Criel, 2019; Finkelstein‐Fox, Park, & Kalichman, 2020; Fuster‐RuizdeApodaca et al., 2019). One pilot experiment showed that PWLH, with higher self‐efficacy for physical exercise, managed their health effectively, since they were likely to engage in physical activities (Mabweazara, Leach, Ley, & Smith, 2018).…”
Section: Introductionmentioning
confidence: 99%